Personalization of politics and political leadership: The cases of the 2012 and 2018 presidential elections in Mexico (Revista de Investigaciones Universidad del Quindío, 2022)
The essential purpose of the paper is to analyze the tendency of personalization of politics in electoral campaigns as a result of the change within party organizations, understood as institutional arrangements and adjustments that political parties have had to assume to remain present in the electoral system. Mexican parties, by maximizing the media visibility of the candidates and their personal qualities, delegating political experience to the background (Rahat, 2015) and, on the other hand, due to the personal political leadership they have developed.     The case studies presented are two. The first is the 2012 presidential election, marking the return to power of the Institutional Revolutionary Party (PRI) with its candidate Enrique Peña Nieto, under a campaign scheme based on the party's structural support, but also due to high media exposure of life personality of a politician with personal charismatic qualities. The second case that is analyzed is the victory of Andrés Manuel López Obrador, it supposes the rise of a recently created political party; National Regeneration Movement (MORENA) who saw in the figure of his candidate the means to be a protagonist of national political life. Both cases represented government alternations and show two contrasting types of political leadership from their origin and in the way they developed their political careers to reach the presidency of the Republic.     It is also important to note that there are exogenous factors that drive partisan change and the emergence of personal political leadership. Among them is the decrease in partisan identities (Moreno, 2009), the volatility of the vote (Díaz and Vivero, 2015) and the increase in the use of digital communication media. All this contributes to the fact that electoral campaigns are in the postmodern stage (Díaz, 2016) characterized by prioritizing the exposure of the personal image of the candidates.
Keywords: political leadership; media; partisan identity; candidates; political trajectory